Small passive object location tracking based on millimeter-wave sensing - Ning WANG; Ke ZHAO; Anfu ZHOU; Huadong MA; Jianhua LIU; Ning YANG (物联网学报)
Since the sensitivity of the millimeter-wave is very strong,the tiny movement of the object can also be sensed by the millimeter-wave as a spectrum change.With this advantage,a small passive object location and tracking method based on the millimeter-wave sensing was provided,which could achieve the high-precision positioning and tracking of target objects.Compared with the traditional active object localization tracking,the target object could not actively transmit signals and the target object was small in the passive object localization tracking.Thus,an effective mechanism was needed to distinguish and separate the reflected signal of the target object and the reflected signal of the background environment.A variety of methods were used to remove the background noise and the burst noise,and a good positioning tracking effect was achieved.The experimental results show that the proposed method can track the movement of a pen with an average error of 0.32 cm.